STUDI AIR TANAH PADA AREA SEMBURAN LUMPUR LAPINDO SIDOARJO MENGGUNAKAN ISOTOP ALAM - Satrio Satrio (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2010)
Groundwater age study has been carried out on mud eruption area in Sidoarjo using natural isotopes. The study was done in 2007 and 2009 by analyzing water samples from mud eruption area. The aim of the study was to identify water characteristics which seeped out from the mud eruption area. Origins of the water can be fossil water, groundwater, or sea water. The 18O, 2H, and d2H data, which were plotted together with d18O data of the water samples of 2007 (LUSI-1 and LUSI-2), showed that water from the center of mud eruption area had interacted with magmatic materials. Whereas, the water from LUSI-3 location which was collected about 300 m distance from the center of mud eruption area had an age of more than 40,000 years, which contained 13C, 18O, and 2H of 1.58o/oo, 5.28o/oo, and -17.5o/oo respectively. This matter indicated that the water was sea water fossil which interacted with magmatic materials. The water in LUSI-4 location had an age of 18,408 years, which contained 13C, 18O, and 2H of -10.5o/oo, 7.68o/oo, and -35.3o/oo respectively. These data indicated that the water was fresh water, which was not mixed with water from mud. The water age from LUSI-5 location was 14,237 years, and contained 13C, 18O, and 2H of -3.00o/oo, -0.25o/oo, and -21.1o/oo respectively. These data showed that the water was partially originated from the groundwater and dominated by mud water. The water age at MVKA location was 14,355 years, and contained 13C, 18O, and 2H of 2o/oo, 2.61o/oo, and -6.6o/oo respectively. This water was estimated as a mixture of mud water and intruded sea water. Plots of 18O, 2H, d2H and d18O, 14C data of water samples of 2009 showed that the water was dominated by groundwater, but the water from LUSI-11 sample was indicated as sea water.